Hubungan Beban Kerja dengan Turnover Intention pada Sumber Daya Manusia Kesehatan di Rumah Sakit Pinna Bekasi Tahun 2025 - Dinda Cahya Cinta; Sarah Geltri Harahap; Yarwin Yari (Jurnal Kesehatan Amanah, 2025)
The high turnover rate of healthcare workers can impact the smoothness and stability of hospital services. This study aims to determine the relationship between the dimensions of workload time load, mental effect load, and psychological stress load with turnover intention in healthcare workers at Pinna Hospital Bekasi in 2025. The study used a quantitative method with a cross-sectional study design, involving 92 respondents selected through total sampling. Data were collected through questionnaires and analyzed univariately and bivariately using the Spearman test. The results showed a significant relationship between workload and turnover intention (p = 0.049), as well as a significant relationship in each workload dimension with turnover intention. Only the psychological stress load dimension had a significant relationship with turnover intention (p = 0.001). Meanwhile, the time load dimension (p = 0.303) and mental effect load (p = 0.394) did not show a significant relationship. The higher the workload, especially psychological stress, the greater the tendency of healthcare workers to intend to change jobs. The results of the bivariate test on the workload variable indicate a positive and significant relationship between workload and turnover intention, a relationship that illustrates that the heavier the workload perceived by healthcare workers, the higher their intention to move or leave their jobs, although the strength of the relationship is relatively weak. Therefore, hospital management is expected to review the work system and pay attention to staff welfare to reduce turnover rates.